ANALISIS FINANCIAL DISTRESS DENGAN MENGGUNAKAN METODE ALTMAN Z-SCORE PADA PERUSAHAAN STARTUP YANG TERDAFTAR DI BEI PERIODE 2020 - 2023 - yosi stefhani; Muhammad Reza Zailindra; Edi Siregar (Jurnal Manajemen, 2026)
The growth of startup companies in Indonesia offers substantial opportunities for the digital economy, yet the increasing failure rate over the past five years reflects heightened financial risks. This study analyzes the financial health of seven startup companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023 using the Modified Altman Z-Score method. A descriptive quantitative approach was applied using secondary financial data. Four key ratios were examined: working capital to total assets, retained earnings to total assets, EBIT to total assets, and book value of equity to total liabilities. Results indicate that PT Elang Mahkota Teknologi Tbk, PT WIR Asia Tbk, PT Indointernet Tbk, and PT Digital Mediatama Maxima Tbk are in the safe zone. However, signs of financial distress appear in PT GoTo Gojek Tokopedia Tbk in 2020 and 2023, as well as PT Solusi Sinergi Digital Tbk, which remained in the grey zone for three consecutive years. Meanwhile, PT Bukalapak.com Tbk shows significant improvement since 2021. The findings highlight that the equity-to-liability ratio is the most influential component in determining the Z-Score and emphasize the need for strengthening capital structure and operational performance to prevent financial distress among startups.